Large-bowel surgery, 1979: self-assessment. Issue 6242 (13th September 1980) - Matheson, N A; Valerio, D
Abstract : Evidence of wide variability in the immediate results of large-bowel surgery stimulated self-assessment during 1979. The hazards of large-bowel surgery can usually be avoided by good bowel preparation, sound anastomotic technique, primary resection in large bowel emergencies, avoidance of anastomosis when hazardous, and antibiotic lavage for extant or potential peritoneal and wound contamination.